Application of MEPBAY for beach stability evaluation: a preliminary test on Rayong Beach, Eastern Thailand - Apichanungkul, Siraset; Pailoplee, Santi; Choowong, Montri (Bulletin of Earth Sciences of Thailand, 2024)
The coastline of Rayong Province, eastern Thailand has been subjected to erosion for decades. Basically, there are two main reasons for erosion, including natural processes such as coastal currents, tides, waves, storms, and monsoons and climate change and human activities such as the failure of sea wall construction. The objective of this study was to apply the MEPBAY program to test the stability of beaches in Rayong Province where several sea walls were constructed. As a result, beaches exhibiting static planform equilibrium remain relatively unaltered except during monsoons. Beaches subject to dynamic equilibrium are primarily situated near river mouths, where their condition hinges on sediment discharge from the rivers. Conversely, the unstable of beaches arises from their reliance on hard structures, necessitating adjustments for the beach to achieve a state of static equilibrium.